Fair, Democratic and Responsible Policies on the Balance Between Central and Regional Financial - Asep Warlan Yusuf (Sociological Jurisprudence Journal, 2018)
Through Law no. 33 of 2004 on Financial Balance between Central and Local Government shall be set up a fair, proportional, democratic, transparent and accountable system of financial distribution. However, the law does not elaborate on the principles of justice, democracy and responsibility. These three principles need to get a more regular, measurable, and measurable legal meaning. In the context of the central-regional fiscal balance policy, the principle of justice manifests in the actions of the central government providing subsidies to each region with a scalable and careful view of the objective conditions of a region, so that in determining the subsidy must be based on considerations acceptable to subsidized area. Democratic principles are realized with the involvement of the community in policy making at the regional level in the form of Provincial/Municipal/Regency Regulations, while the principle of responsibility is manifested through the limitation of government power by legal means. Government power in governance is directed to the implementation of Good Government Governance (GGG).